Effect Of Firm Specific’s On Financial Performance Of Financial Sector With Moderating Role Of Corporate Social Responsibilities - Shumaila Israr , Syed Muddasir Hussain , Basit Ali , Gul Sanga , Dilshad Khan , Arjumand Farooq (Migration Letters, 2024)
Constant cycles of banking and financial crises uncover the complexity and frailty of the financial and banking system. Firm specifics with the moderated role of CSR and their impact on the financial performance of banks from 2014 to 2023 have been empirically studied by the authors. This research explores associations of selected key firm characteristics (leverage, size, age, and tangibility) and profitability with moderating Corporate Social Responsibility (CSR). The research used correlation, regression, and moderation analysis to find the impact of these variables alone and the combined impact on firm profitability. We find a negative but insignificant relationship between leverage and profitability suggesting that debt levels are not an important driver of profitability in the sample firms, in line with pecking order theory. However, contrary to other schools of thought, independently of the tangibility, firm profitability is positively and significantly associated with firm size and age in support of the resource based view (RBV) that emphasizes that firm specific assets increase a Bank’s financial performance. The analysis result analyzing the moderation indicates that CSR serves a dual role acting to substitute or complement. Leverage reduces profitability through the substitution effect, and size, age and tangibility increase profitability via complementary effect, both of which is mitigated by CSR. The results are consistent with stakeholder theory and shared value theory, arguing that integrating CSR into firm strategy contributes to their success. The results of this study are valuable for gaining insight into the firm performance dynamics and making theoretical and practical implications for corporate governance and strategy.